Age-related changes in the viscoelasticity of rabbit lens characterised by surface wave dispersion analysis. (January 2022) - Zhang, H; Singh, M; Zvietcovich, F; Larin, K V; Aglyamov, S R
Abstract: The viscoelastic properties of the young and mature rabbit lenses in situ are evaluated using wave-based optical coherence elastography (OCE). Surface waves in the crystalline lens are generated using acoustic radiation force (ARF) focused inside the eyeball. Surface-wave dispersion is measured with a phase-stabilised optical coherence tomography (OCT) system. The Young's modulus and shear viscosity coefficient are quantified based on a Scholte wave model. The results show that both elasticity and viscosity are significantly different between the young and mature lenses. The Young's modulus of the lenses increased with age from 7.74 ± 1.56 kPa (young) to 15.15 ± 4.52 kPa (mature), and the shear viscosity coefficient increased from 0.55 ± 0.04 Pa s (young) and 0.86 ± 0.13 Pa s (mature). It is shown that the combination of ARF excitation, OCE imaging, and dispersion analysis enables nondestructive quantification of lenticular viscoelasticity in situ and shows promise for in vivo applications.